Pelatihan Penanganan Cedera Kepala dan Perawatan Luka Bagi Guru dan Siswa SD IT Hafizul ‘Ilmi Aceh - Ahyana; Aklima; Riski Amalia; Nani Safuni (LSM Catimore dan Sahabat, 2023)
It is crucial that teachers and students at SD IT Hafizul 'Ilmi Gampong Blang Krueng have the knowledge and abilities to deal with head injuries and treat minor injuries. This information may assist teachers and students cope with any head injuries that arise in the school environment. Both by the teachers and the students themselves. In addition to having the ability to treat minor injuries from falls, brain injuries such migraines, concussions, skull fractures, seizures, and wound care are common in schools. The goal of this community service project was to improve teachers' and students' knowledge and expertise in addressing head traumas and wound care. This act of community service was a component of a campaign to support the cadres and teachers working on UKS (School Health Division) SD IT Hafizul 'Ilmi.